Value-Added, Energy and Technology-Capital in Central Java Industries - Wahyudi, Setyo Tri; Darmawan, Darmawan (Jurnal Ekonomi & Studi Pembangunan, 2021)
Nowadays, many industries do not depend on labor intensive, but have transformed to rely on intensive technology. Industry is considered potential strategy to raise value-added for its effort to alter raw or intermediate goods to finished goods. In this study, value-added approach is used to measure the role of technology - capital and energy. A lot of work has been done analyzing restricted variables in single study, but there is still a significant gap where research did not determine differences between measures. This paper aims to discuss the similarities of many technology – capital and energy related variables in Central Java Industries and analyzes their profile change to regional value-added from 2007 to 2017. Data related to technology – capital and energy are collected from Statistics Indonesia (Badan Pusat Statistik). The variables are examined using exploration factor analysis, multiple linear regression, and cluster analysis. The result shows that the energy consumption has the greatest effect on value-added rising during the study period, while technology - capital does not. Hence, policymaker should maintain the availability of energy for industries. Then, except for Kudus Regency and Semarang Municipality, policymaker should pay attention to the growth of value-added of the entire regions.